The Nooter photo collection and the Roots2Share project of museums in Greenland and the Netherlands - Buijs, Cunera; Jakobsen, Aviâja (Études/Inuit/Studies, 2011)
In 2008 two Dutch museums and two Greenland museums started a cooperative venture to share the photo collections of museums in the Netherlands. The photographs were taken from 1965 to 1986 by husband and wife Gerti and Noortje Nooter in Diilerilaaq, a village in the Sermilik Fjord (East Greenland). Gerti Nooter, then curator at the Museon in The Hague and at the National Museum of Ethnology in Leiden, was doing fieldwork in that changing hunting community and, as part of that research, took photographs and collected museum objects for both Dutch museums. The National Museum of Ethnology in particular has long had a working relationship with Greenland museums and the local Tunumiit community. Through the visual repatriation project Roots2Share, these photographs have been scanned and returned to the communities where they originated and where they can now be accessed locally. As a product of cross-cultural interactions, they depict ancestors of present-day Tunumiit and carry multiple meanings: ethnological or exotic ones for a Dutch public and historical or ancestral ones for the people of Diilerilaaq. Many stories have been told about them. This article explores the relationship between the photographs and Tunumiit knowledge, as well as issues of cultural heritage, ownership, and sharing of these images.